2000
DOI: 10.1016/s0378-1097(00)00105-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Neurospora crassa heat shock factor with the heat shock element during heat shock and different developmental stages

Abstract: The interaction of the heat shock factor (HSF) with the heat shock element (HSE) was determined by a non-radioactive electrophoretic mobility shift assay, in order to analyze HSF regulation in Neurospora crassa. HSF binds to HSE under normal, non-stress conditions and is thus constitutively trimerized. Upon heat shock, the HSF^HSE complex shows a retarded mobility. This was also observed in Saccharomyces cerevisiae, where this mobility shift was shown to be due to HSF phosphorylation [Sorger and Pelham (1988) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…For Neurospora, HSE are not yet well defined, but nGAAn .. nTTCn motifs (where "n" can be any nucleotide) are present in the promoters of hsp30 (38) and hsp70 (21). Additionally, a factor in Neurospora protein extracts binds specifically to labeled oligonucleotides containing the classic yeast HSF binding sequence nTTCnnGAAnnTTCn (32). Band shift assays with purified Neurospora HSF(s) should aid in the identification of the discriminating consensus binding sites for HSF1 and HSF2.…”
Section: Discussionmentioning
confidence: 99%
“…For Neurospora, HSE are not yet well defined, but nGAAn .. nTTCn motifs (where "n" can be any nucleotide) are present in the promoters of hsp30 (38) and hsp70 (21). Additionally, a factor in Neurospora protein extracts binds specifically to labeled oligonucleotides containing the classic yeast HSF binding sequence nTTCnnGAAnnTTCn (32). Band shift assays with purified Neurospora HSF(s) should aid in the identification of the discriminating consensus binding sites for HSF1 and HSF2.…”
Section: Discussionmentioning
confidence: 99%
“…The HSF of N. crassa has been shown to bind constitutively to HSEs under nonstress conditions while heat shock induced an alteration in HSF which led to its fast inactivation (Meyer et al , 2000; Monnerjahn et al , 2001).…”
Section: Hsps and Nonpathogenic Fungimentioning
confidence: 99%
“…Despite the lack of nucleotide-resolution studies characterizing these hse as functional, their sequence identity strongly suggests that these regions are conserved and are likely recognized by HSFs, commanded by the major regulator in Neurospora : HSF-1 (NCU08512). In addition, it has been shown that the HSF of Neurospora can efficiently recognize a hse from yeast [81]. Based on this, we used one of the HSF-1 motifs obtained from yeast and N. crassa to further identify new, and confirm the previously proposed hse in the hsp30 promoter (Tabla S2, S3).…”
Section: Discussionmentioning
confidence: 63%